2009
DOI: 10.1039/b814379j
|View full text |Cite
|
Sign up to set email alerts
|

Dye displacement assay for saccharide detection with boronate hydrogels

Abstract: Hydrogel spheres, fashioned from an operationally simple mould, that incorporate boronate units were shown to function as saccharide sensors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(44 citation statements)
references
References 28 publications
(26 reference statements)
1
43
0
Order By: Relevance
“…Indicator displacement has recently gained new ground via a sensing motif based on dye displacement using boronate hydrogels [28•]. Making use of a new development, boronate affinity in saccharide electrophoresis, or BASE, that relies on the modulation of saccharide mobility within a flexible porous hydrogel, the group went on to quantitatively detect a wide range of fructose concentrations at physiological pH; the indicator displacement scheme used can be seen in Figure 3.…”
Section: Colorimetric Sensors and Sensing Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indicator displacement has recently gained new ground via a sensing motif based on dye displacement using boronate hydrogels [28•]. Making use of a new development, boronate affinity in saccharide electrophoresis, or BASE, that relies on the modulation of saccharide mobility within a flexible porous hydrogel, the group went on to quantitatively detect a wide range of fructose concentrations at physiological pH; the indicator displacement scheme used can be seen in Figure 3.…”
Section: Colorimetric Sensors and Sensing Methodsmentioning
confidence: 99%
“…In many cases, phenylboronic acids are coupled with chromophores to give a color response to binding of the boronic acid moiety. In this manner, several color changing motifs have been utilized including, indicator displacement [26••,27-28•], boronic acid appended chromophores [24,29-32•], and pH induction [33,34••], and these have been extended to produce differential sensing platforms optimized to human body temperature and physiological pH [23,35-37]. …”
Section: Interactions Between Boronic Acids and Diolsmentioning
confidence: 99%
“…The advantage of this method is that the indicator is not covalently attached to receptor, and it is possible to change receptors and indicators at will [21,22]. IDA has been used in competitive binding assays of saccharides in fluorescent and colorimetric sensing system [23][24][25]. A typical kind of fluorescent saccharide sensing system which is similar to an IDA has been achieved based on the formation of a ground-state complex between fluorophores such as fluorescent dye [26] or graphene quantum dots [27], and boronic acid appended bipyridinium salts.…”
Section: Introductionmentioning
confidence: 99%
“…Research discussed earlier has shown that ARS can competitively bind with boronic acids in the presence of sugars. [23][24][25] We explored using ARS as well as hydrophobic analogs of this chromophore that could be maintained within the sensor. Sensors containing alizarin demonstrated the greatest percent change in fluorescence when in the presence of glucose, and their fluorescence intensity remained stable over time.…”
Section: As Is Shown Inmentioning
confidence: 99%
“…When glucose is introduced into the system, glucose binds with the boronic acid, displacing the alizarin which renders it nonfluorescent. Competitive binding of this sort has been used in the development of other saccharide sensors 23,25 and exploits the well-established affinity of boronic acids for diol moieties. 26,27 Unlike other assays using this principle, our sensor components are encapsulated in a hydrophobic polymeric membrane imparting such benefits as decreased interference from other biomolecules, 17 the use of nonbiological components, and sensor reversibility.…”
Section: Introductionmentioning
confidence: 99%